The Discourse of Control - Maguire, Stephen (Journal of business ethics, 1999)
I challenge the appropriateness of the discourse of managerial control of employees in four ways. First, I question arguments which suggest that employees are always subject to organizational control. Second, I contrast workplace conditions which support employee self-determination and autonomy with conditions which permit control of employees. Third, I provide an ethical assessment of the normative use of control talk and fourth, I suggest an alternative discourse, a discourse of accountability which appropriately highlights the reciprocity necessary to build ethical organizations.